Interactive methods of teaching the Uzbek language - Kholmukhammedova Umida Rasulovna (Genius Publishing Group, 2022)
The use of interactive methods in the professional training of students involves the formation of critical thinking implying a variable, independent, meaningful position. This position significantly increases the reliability of education, because it becomes conscious and reflexive and increases the communicative potential of the individual.
Keywords: Teaching Method; Interactive; Interaction; Creative Task